2008
DOI: 10.1093/jnci/djn260
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma Skin Cancer and Risk for Subsequent Malignancy

Abstract: This community-based, prospective cohort study provides evidence for an association between an NMSC diagnosis and an increased risk of subsequent cancer, even after adjusting for individual-level risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 28 publications
7
78
2
1
Order By: Relevance
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 88%
See 1 more Smart Citation
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 88%
“…Our previous study has reported an increased risk of cancer including melanoma in association with history of KC in the Nurses' Health Study (NHS;1984-2008 and Health Professionals Follow-up Study (HPFS;1986-2008 (18). However, this previous report did not examine the detailed subgroups of KC in association with the risk of developing melanoma and melanoma subtypes, did not investigate the impact of multiple KCs on melanoma risk, and did not investigate the potential modification of the KC-melanoma association by other melanoma risk factors.…”
mentioning
confidence: 99%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified
“…Furthermore, a recent study showed that individuals with a history of NMSC may be at a greater risk of going on to develop other types of cancer. 9 The principal cause of skin cancer is excessive exposure to ultraviolet radiation (UVR), solar radiation being the principal source. Other risk factors that appear to be involved with the development of NMSC include mutations in regulatory genes, exposure to ionizing radiation, arsenic, polyaromatic hydrocarbons and changes in the immune system, among others.…”
Section: Introductionmentioning
confidence: 99%